The lesbian fantastic a critical study of science fiction, fantasy, paranormal and gothic writings - Betz, Phyllis M. (Phyllis Marie), 1953- (McFarland & Co., Publishers, 2011)
"This work examines how lesbian authors have used the structures and conventions of science fiction to embody characters, relationships and other themes that relate to their experience as the quintessential Other in the broader culture. Topics include lesbian gothic, fantasy, science fiction, mixed genre texts and historical background. A vital addition to the scholarship on homosexuality and culture"--Provided by publisher.